From metabolic byproduct to immune modulator: the role of lactate in tumor immune escape - Jiang, Mengqian; Wang, Yuanchun; Zhao, Xiaoyong; Yu, Jinming (Frontiers in Immunology, 2024)
Lactic acid, a key metabolic byproduct within the tumor microenvironment, has garnered significant attention for its role in immune evasion mechanisms. Tumor cells produce and release large amounts of lactic acid into the tumor microenvironment through aberrant glycolysis via the Warburg effect, leading to a drop in pH. Elevated lactic acid levels profoundly suppress proliferation capacity, cytotoxic functions, and migratory abilities of immune effector cells such as macrophages and natural killer cells at the tumor site. Moreover, lactic acid can modulate the expression of surface molecules on immune cells, interfering with their recognition and attack of tumor cells, and it regulates signaling pathways that promote the expansion and enhanced function of immunosuppressive cells like regulatory T cells, thereby fostering immune tolerance within the tumor microenvironment. Current research is actively exploring strategies targeting lactic acid metabolism to ameliorate tumor immune evasion. Key approaches under investigation include inhibiting the activity of critical enzymes in lactic acid production to reduce its synthesis or blocking lactate transporters to alter intracellular and extracellular lactate distribution. These methods hold promise when combined with existing immunotherapies such as immune checkpoint inhibitors and chimeric antigen receptor T-cell therapies to enhance the immune system’s ability to eliminate tumor cells. This could pave the way for novel combinatorial treatment strategies in clinical cancer therapy, effectively overcoming tumor immune evasion phenomena, and ultimately improving overall treatment efficacy.